Challenges of teaching through web-based inquiry: a longitudinal case study of a veteran high school teacher - Iolie Nicolaidou; Kyza, Eleni A. (My University, 2012)
This case study follows a veteran biology teacher, as she pursued the integration of technology-supported inquiry over the period of three years. The teacher was involved in the design and enactment of a web-based inquiry learning environment. Multiple data collected included videotapes of all the enactments, teacher interviews and videotapes of all design meetings. Teacher challenges relating to inquiry and technology during the design and enactment of web-based inquiry are presented and discussed. ISLS.
Keywords: Computer aided instruction; High school teachers; Longitudinal case study; Multiple data; Web-based inquiry learning; Design; Education; Video recording; Websites